Performance of Village-Owned Enterprises in East Lombok Regency Using the Structural Equation Modelling (SEM) Approach - Sahrul Ihsan; Muhamad Sarlan (LP2M IAIN Palopo, 2025)
To alleviate poverty and reduce economic inequality, one of the government's strategic steps is to establish Village-Owned Enterprises (BUMDes) in each village and maximize the use of village funds. BUMDes are expected to become a driving force for the local economy by managing the village's potential resources. Although designed as a strategic program for village development and empowerment, in practice, many BUMDes face difficult situations and do not deliver optimal results. The main problems faced by BUMDes in East Lombok Regency include unprofessional management, limited human resources, and minimal training and technical guidance. The objectives of this study are: 1) To determine the factors that influence the performance of Village-Owned Enterprises (BUMDes) and 2) To determine the direct, indirect, and total influence of indicators on the performance of Village-Owned Enterprises in East Lombok Regency. The method used is descriptive quantitative analysis. The determination of sample locations was determined purposively as much as 50 percent of the number of BUMDes in East Lombok Regency or as many as 120 BUMDes units taken by cluster random sampling method. Data analysis used the Structural Equation Model (SEM) PLS version 4.0. The results of the study show (1) The factors that have a very large effect on the performance of Bumdes in East Lombok Regency are leadership and governance. While government support and human resource management have a very small effect on Bumdes performance. (2.) The factors that directly influence Bumdes performance are government support, human resource management and governance. While leadership does not have a significant direct effect on Bumdes performance. (3) The factors that indirectly influence Bumdes performance mediated by governance are government support and leadership. While human resource management mediated by governance does not have a significant effect on Bumdes performance. Furthermore, the total influence on Bumdes performance is government support, leadership, human resources and governance. While human resource management does not have a significant effect on Bumdes governance.